SPECIFIC PHOBIAS AND PANIC ATTACKS: ANALYSIS OF COGNITIVE RESTRUCTURING TECHNIQUES (International Seven Journal of Multidisciplinary, 2022)
This article presents a qualitative literature review on the application of cognitive behavioral therapy in the management of specific phobias and panic attacks, with an emphasis on cognitive restructuring techniques. The data showed that gradual exposure, combined with the identification and modification of automatic thoughts, consistently reduces symptoms and leads to overall improvement in patients’ functioning. It was found that psychoeducation, coping skills training, and the use of technologies such as virtual reality enhance the therapeutic process and increase safety during interventions. The results revealed a positive impact in both individual and group sessions, contributing to greater self-confidence, reduced avoidance behaviors, and social reintegration. Thus, it is concluded that cognitive behavioral therapy stands out as the treatment of choice for these conditions, promoting stable cognitive and behavioral changes and significantly improving quality of life.